Early Adoption of Checkpoint Inhibitors in Patients with Metastatic Gastric Adenocarcinoma—A Case Series of Non-Operative Long-Term Survivors - Dalia Kaakour; Garrett Ward; Farshid Dayyani (Diseases, 2022)
Checkpoint inhibitor (CPI) therapy has only recently been introduced in the first-line treatment of advanced gastric cancer. However, later line monotherapy CPI efficacy in a subset of patients was presented about four years prior. Here, we present three cases of advanced gastric adenocarcinoma cancers treated with CPI in early lines years prior to the availability of randomized first line data. All three patients remain in remission without gastrectomy, with the median time from initial diagnosis of approximately 52 months. With long-term follow-up of more than four years, we present a proof of concept that, with early integration of CPI therapy, highly durable responses are possible even in the absence of surgery in patients with advanced gastric and gastroesophageal junction cancers.